KANTOR PUSAT BADAN EKONOMI KREATIF DENGAN PENDEKATAN ARSITEKTUR BERKELANJUTAN DI JAKARTA - Daniel Tantama Putro; Hardiyati Hardiyati; Leny Pramesti (Universitas Sebelas Maret Surakarta, 2016)
ASEAN Economy Community is a great opportunity for each country in ASEAN to expand its economy. These opportunities are not only related to trade market, but also in services market, experts, investment and capital flows. However behind these opportunities, not a few countries in ASEAN respond the open market or free market of ASEAN become a threat. Badan Ekonomi Kreatif (Bekraf) was established as a government effort to overcome ASEAN free market, which creative economy is Indonesia economy focus nowadays. Since was establishes at early 2015, Bekraf has been quite instrumental in moving the creative economy in Indonesia. Headquarter planning becomes important not only to facilitate Bekraf, but also supports the development of creative economy in Indonesia to compete in the free market of ASEAN. But now in the planning and design issues have become more widespread, namely environmental problems. Jakarta as government center, the location of the site is a crowded city, have limited land, little green open space, and a variety of other environmental problems. These conditions make the construction of new buildings in Jakarta becomes irrelevant. Sustainable Architecture approach is right solution because this approach has the ability to address environmental issues with sustainable resources which aims to improve the quality of the natural and human. The problem in this design is how to present principle of Sustainable Architecture at office and commercial building typology. Planning and design Bekraf Headquarter use connectivity, indigenous, and long life, loose fit methods which are three principle of Sustainable Architecture. Design applications of Sustainable Architecture at Bekraf Headquarter processed through strategy of Sustainable Architecture, those are sustainable land use, sustainable material, sustainable energy, sustainable water, sustainable health and well-being, and sustainable community. The strategy of Sustainable Architecture building design embodies a minimal pavement at the site, the contours of landscape, using modular and renewable materials, rosters design and mass openness to optimize cross ventilation and natural lighting, wastewater treatment pond design, structuring elements of vegetation, accessibility design, building automation systems, as well as the design of corridors into public spaces. Keywords: Badan Ekonomi Kreatif, Connectivity, Creative Economy, Indigenous, Long Life, Loose Fit, Sustainable Architecture